Juozas Krikštaponis (Krištaponis): The Question of Participation in the Holocaust and the Problem of Historical Memory - Pocius, Mindaugas (Genocidas ir rezistencija, 2022)
Based on the documents available in the Lithuanian Special Archives and the Lithuanian Central State Archives, and on critical analysis of other sources, the article presents an attempt to reveal some features of biography of Juozas Krikštaponis (Krištaponis), commander of Vytis District, also his activities during the Nazi occupation which are little known to the public, and to answer the question of whether he was involved in the mass killings of Jews and other civilians. The article unveils and examines the complex, unexpected institutional and social complications that have arisen in the evaluation and historical memory of Krikštaponis’ (Krištaponis’s) activities, which mark the encounters between the collective memory of Holocaust and guerrilla resistance in the modern society. The paper also provides an analysis of actions and attitudes of individual actors of memory and summary of their position. Analysis of the use of personal name Juozas Krikštaponis’ (Krištaponis’) in different sources leads to the reasonable conclusion that his real personal name was Juozas Krištaponis. After the restoration of independence, the erroneous use of Juozas Krikštaponis can be seen in Soviet and partisan documents instead of the real name Juozas Krištaponis due to different variations (clerical mistakes) of the 2nd Battalion of Auxiliary Police Service (APS). According to historical research, the 2nd APS battalion of the Order Police of the Reich Commissariat Ostland shot more than 15,000 Jews in more than 15 locations in Belarus between October and December 1941. All three companies (the 1st, the 2nd and the 3rd) of the 2nd APS Battalion took part in the massacre. Besides, in the period from October to November 1941, in approximately six campaigns, the 2nd APS Battalion shot at least 2,360 prisoners of the prisonerof- war camp Stalag No. 352 in Minsk. All three companies of the 2nd APS battalion participated in the massacre of the prisoners of war. A critical analysis of the testimonies of the former policemen of the 2nd APS Battalion and of some other sources leads to the reasonable assertion that in August–December 1941 Lt. Juozas Krikštaponis (Krištaponis) and Lt. Nikodemas Reikalas were alternately serving as commanders of the 2nd Company of the 2nd Battalion. Krikštaponis (Krištaponis) commanded the 2nd Company from 1 August to the end of October and in December, meanwhile, Reikalas – from the end of October to the end of November. It can be also reasonably stated that Krikštaponis (Krištaponis) was in command of the 2nd Company of the 2nd APS Battalion on 10 October 1941, when prisoners of the Jewish ghetto in Rudzensk were killed and on 15–16 October 1941 when prisoners of the prisoner-of-war camp Stalag No. 352 were shot, meanwhile, Lt. Reikalas commanded the 2nd Company during the massacre of the prisoners of the Jewish ghetto in Slutsk, Kletsk, Minsk and Borisovat the end of October–November 1941. The problem of commemorating the historical memory of Juozas Krikštaponis (Krištaponis) (the status of a volunteer soldier, the rank of colonel, the award of the 1st degree Order of the Cross of Vytis, the memorial stone in Ukmergė, the name of the street in Panevėžys) speak of the past systemic errors of the state’s history policy and of the absence (or lack) of political will of the current leadership of some state institutions. At the same time, it testifies to the absence of coherence between the collective memories of the Holocaust and the anti-Soviet partisan resistance, the immaturity of the historical consciousness of a part of the society, the indifference and the lack of common human ethical values. Evaluation of Juozas Krikštaponis’ (Krištaponis’) biography and personality, the decisions adopted by authorities or their inaction in relation to his historical memory serve as an indicator which shows or will show in the future the level of reflection (self-awareness) and consciousness of the leaders of state institutions and of our society, the state of the collective memory of the Holocaust, and of the state of historical policy of the country.